2022
DOI: 10.5114/ceji.2022.120618
|View full text |Cite
|
Sign up to set email alerts
|

Immune cell-specific smoking-related expression characteristics are revealed by re-analysis of transcriptomes from the CEDAR cohort

Abstract: Introduction: smoking is known to affect whole-blood expression and methylation profiles. although whole-genome methylation studies indicated that effects observed in blood may be driven by changes within leukocyte subtypes, these phenomena have not been explored using expression profiling.Material and methods: this study reanalyzed data from the Correlated Expression and Disease association research (CEDar) patient cohort recruited by momozawa et al. (E-mtab-6667). Data from gene expression profiling of immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 75 publications
(111 reference statements)
1
1
0
Order By: Relevance
“…60 Besides, smoking can increase the expression of CLEC5A in immune cells. 61 Wortham et al demonstrated that CLEC5A was highly expressed on alveolar macrophages in mouse models of COPD and human longterm smokers, while it was almost not expressed in macrophages of healthy controls, 62 which was consistent with our findings. What's interesting was that Sung et al found that thrombotic inflammation was attenuated dramatically in clec5a−/− mice, 63 based on which we dared to speculate that perhaps the high expression of CLEC5A is a major risk factor for embolism in COPD patients.…”
Section: Discussionsupporting
confidence: 92%
“…60 Besides, smoking can increase the expression of CLEC5A in immune cells. 61 Wortham et al demonstrated that CLEC5A was highly expressed on alveolar macrophages in mouse models of COPD and human longterm smokers, while it was almost not expressed in macrophages of healthy controls, 62 which was consistent with our findings. What's interesting was that Sung et al found that thrombotic inflammation was attenuated dramatically in clec5a−/− mice, 63 based on which we dared to speculate that perhaps the high expression of CLEC5A is a major risk factor for embolism in COPD patients.…”
Section: Discussionsupporting
confidence: 92%
“…They also related to IL1 signaling: possible recruitment of IKK complex by interleukin 1 receptor associated kinase 1 ( IRAK1 ) and interleukin 18 binding protein ( IL18BP ) interference with signaling via IL18 (which belongs to IL1 family). One of the top positive correlates of RUNX3 was C-type lectin domain containing 16A ( CLEC16A ) of a group of proteins related to (auto)immunity and IBD [ 61 ].…”
Section: Discussionmentioning
confidence: 99%